The Role Of MSME Marketing Strategy In Achieve Competitive Advantage: Peran Strategi Pemasaran UMKM Dalam Mencapai Keunggulan Kompetitif - Lailla, Nor; Sriminarti, Nurul (Universitas Muhammadiyah Sidoarjo, 2022)
MSMEs contribution to economic growth makes the MSMEs perfomance need to be improved. In the case a number of factors: product, promotion, price, distribution channel, digital marketing must be considered to improve the perfomance in MSMEs, enterpreneur ship and market orientation, so the aim of this research is provide concept marketing strategy in achieve competitive advantage. This research is use qualitative through interview with MSME. The result of this study is provide consept business strategic that can be praticed by MSMEs will improve competitive advantage. The strategic concept design include: improvement of product and service quality, attract consumers with promotion, specify of price, decide distribution channel, digital marketing. The consep of this marketing strategy can be use UMKM in changing conditions of competitive advantage.